2013
DOI: 10.1021/jp406928v
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Thermoelectric Properties of the Mineral FeS2: An Ab Initio Study

Abstract: First principles calculations were carried out to study the phase stability and thermoelectric properties of the naturally occurring marcasite phase of FeS 2 at ambient condition as well as under pressure. Two distinct density functional approaches has been used to investigate the above mentioned properties. The plane wave pseudopotential approach was used to study the phase stability and structural, elastic, and vibrational properties. The full potential linear augment plane wave method has been used to study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 86 publications
6
41
1
Order By: Relevance
“…This approximation assumed that the scattering time determining the electrical conductivity would not vary strongly with energy on the scale of kT. This method has been widely used to calculate transport properties of thermoelectric materials [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Computational Detailsmentioning
confidence: 99%
“…This approximation assumed that the scattering time determining the electrical conductivity would not vary strongly with energy on the scale of kT. This method has been widely used to calculate transport properties of thermoelectric materials [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this package, the grid of T is dened by T max in the input le. [38][39][40][41] 3. In RBA, it is assumed that the band structure of the host is unchanged by doping.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In earlier studies, the phase stability and thermoelectric properties of the naturally occurring marcasite phase of FeS2 under ambient conditions has been investigated using firstprinciples calculations. 18,25 Total energy calculations show that marcasite FeS2 was stable at ambient conditions, and that it undergoes a first-order phase transition to pyrite FeS2 at around 3.7−5.4 GPa at 0 K. 18, 25 Reich and Becker have also employed first-principles and Monte Carlo calculations to investigate the thermodynamic mixing properties of arsenic into bulk pyrite and marcasite. 26 From their calculated enthalpies, configurational entropies and Gibbs free energies of mixing, it was shown that the two-phase mixtures of FeS2 (pyrite or marcasite) and FeAsS (arsenopyrite) are energetically more favorable than the solid solution Fe(S,As)2 (arsenian pyrite or marcasite) for a wide range of geologically relevant temperatures.…”
Section: Introductionmentioning
confidence: 99%